CITED2 in breast carcinoma as a potent prognostic predictor associated with proliferation, migration and chemoresistance. Issue 12 (1st December 2016) - Minemura, Hiroyuki; Takagi, Kiyoshi; Sato, Ai; Takahashi, Hikaru; Miki, Yasuhiro; Shibahara, Yukiko; Watanabe, Mika; Ishida, Takanori; Sasano, Hironobu; Suzuki, Takashi
Abstract : CITED2 (Cbp/p300‐interacting transactivator, with Glu/Asp‐rich carboxy‐terminal domain, 2) is a member of the CITED family and is involved in various cellular functions during development and differentiation. Mounting evidence suggests the importance of CITED in the progression of human malignancies, but the significance of CITED2 protein has not yet been examined in breast carcinoma. Therefore, in the present study, we examined the clinical significance and the biological functions of CITED2 in breast carcinoma by immunohistochemistry and in vitro study. CITED2 immunoreactivity was detected in breast carcinoma tissues, and it was significantly higher compared to those in morphologically normal mammary glands. CITED2 immunoreactivity was significantly associated with stage, pathological T factor, lymph node metastasis, histological grade, HER2 and Ki‐67, and inversely correlated with estrogen receptor. Moreover, the immunohistochemical CITED2 status was significantly associated with increased incidence of recurrence and breast cancer‐specific death of the breast cancer patients, and multivariate analyses demonstrated CITED2 status as an independent worse prognostic factor for disease‐free and breast cancer‐specific survival. Subsequent in vitro experiments showed that CITED2 expression significantly increased proliferation activity and migration property in MCF‐7and S KBR‐3 breast carcinoma cells. Moreover, CITED2 caused chemoresistance to epirubicin and 5‐fluorouracil, but not paclitaxel, in these cells, and it inhibited p53 accumulation after 5‐fluorouracil treatment in MCF‐7 cells. These results suggest that CITED2 plays important roles in the progression and chemoresistance of breast carcinoma and that CITED2 status is a potent prognostic factor in breast cancer patients. Abstract : This is the first report that examined CITED2 protein in human breast carcinoma. Results of our immunohistochemical study demonstrated that the CITED2 status was an independent worse prognostic factor of the patients, and in vitro studies indicated that CITED2 promoted cell proliferation, migration and chemoresistance in breast carcinoma cells. These results suggest a pivotal role of CITED2 in breast carcinoma, and CITED2 could become an important prognostic marker and therapeutic target to improve clinical outcome of breast cancer patients.